Comparison of beamforming algorithms based on localization of calibrating sound sources and air jet noise - Ershov, V; V. Palchikovskiy, V (International Journal of Engineering and Technology, 2018)
The paper considers study of beamforming algorithms for localization of noise sources. The mathematical formulations are briefly described for the following algorithms: Delay-and-Sum Beamforming, Cross-spectral Beamforming, Deconvolution Approach for the Mapping of Acoustic Sources (DAMAS). Based on the mentioned algorithms the program codes were developed. Operability of the program codes was tested on virtual localization of the point sources. All algorithms demonstrated good ability to distinguish these sources at different frequencies at their close position relative to each other. Initially, experiments were based on localization of calibrating static sound sources (beepers) using BruelÂ &Â Kjaer 54-microphone array. The measured data were processed both in the BruelÂ &Â Kjaer software and in the developed software. For static point sources, all algorithms have shown good work quality. The experiments were also carried out for the localization of noise sources in a turbulent air jet. In this case, the best results were demonstrated by Cross-Spectral Beamforming algorithm.Â Â